Personal Character and Stigma in the Acceptance Process of Families Caring for Individuals with Mental Disorders - Priasmoro, Dian Pitaloka; Dradjat, Respati S.; Zuhriyah, Lilik; Asri, Yuni (Journal of Nursing Science Update (JNSU), 2024)
Mental illness necessitates long-term care, impacting both sufferers and their families due to societal stigma. This study examined the correlation between personal character and self-acceptance, stigma, and self-acceptance, and the sociodemographic factors influencing acceptance. The study used a quantitative descriptive design to analyze data from 130 individuals who were purposefully selected from a total population of 175 families with members experiencing mental disorders. The research instruments included standard questionnaires to measure personal character, extraversion, perceived stigmatization, stigma, and family adaptation acceptance. Results indicated that personal character and stigma were significantly associated with acceptance (p-value <0.05). At the same time, the distance to the health center was the most influential demographic factor (p-value <0.005, Chi-Square 170.071). In conclusion, strengthening the personal character of families is crucial to mitigate the negative impact of societal stigma. Furthermore, enhancing services provided through health centers is essential.